Growth and nutritional disorders of eggplant cultivated in nutrients solutions with suppressed macronutrients - Flores, Rilner Alves [UNESP]; Montes Nogueira Borges, Bernardo Melo [UNESP]; Almeida, Hilario Junior [UNESP]; Prado, Renato De Mello [UNESP] (Taylor & Francis Inc, 2015)
The objective was to evaluate the effects of omitting macronutrients in the nutrients solution on growth characteristics and nutritional status of eggplants. The treatments were complete nutrients solution and solutions with nutrient omission: nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sulfur (S). The experiment was carried out under greenhouse conditions with three replicates in a completely random design. Plant height, number of leaves per plant, leaf area, relative chlorophyll index, photosynthesis rate, stomatal conductance, dry matter, concentration levels of macronutrients in plant aerial part and root system, and nutritional disorders were evaluated. Omitting elements interfered in the concentration of elements in the various plant tissues and this had as consequences limited vegetative growth, reduced dry matter and led to the development of the typical deficiency symptoms of each element. Although potassium was the most demanded of all elements, nitrogen and calcium were the most growth limiting ones.
Keywords: Mineral nutrition; Solanum melongena; Nutritional deficiency